Evaluating the extend of marketing plan in Nigerian business organization - Ogu, Sokari Jusih (Journal of Commerce, Management, and Tourism Studies, 2024)
This study assessed the extent to which Nigerian firms planed their marketing programmes and also the extent of formalization of marking planning. It was found that some forms of planning were in operation among many firms. However, only one-third of the firms of studied adopted a comprehensive, formalized, approach, and this was found to be a function of size of operation – large firms tended to do so. We further found that nearly half of the firms prepared forecasts and budgets in lieu of marketing plans, and this was attributed to the intellectual rigour involved in marketing planning. It has been recommended, among other measures that, experienced professionals be always appointed to head the marketing function in business organizations. The population for this study consisted of firms in Lagos employing 50 or more persons engaged in manufacturing or distributive trade. Only such firms listed in the 1986 edition of the Lagos state industrial Directory were included. For the purpose of this study, we classified the firms into categories, A, B, C, as small categories, D and E as medium, and categories F, G, H and I, as large. This implies that we focused attention on categories D to I while ignoring categories A to C. Our concentration on medium-large firms is borne out of our conviction that their size of operations may necessitate the need for elaborate planning.